Industrial feeding in Finland in 1970 - Laakkonen, Eini (Agricultural and Food Science, 1974)
A questionnaire was distributed to the customers of industrial canteens. This contained questions concerning the composition of the meal eaten by the Worker on the day of the inquiry, as well as questions concerning his breakfasts in general, his likes and dislikes, etc. The employers Were asked about the annual food consumption figures of their canteens, menus and menu planning, kitchen facilities, education of the kitchen personnel, etc. The nutritive value of meals was estimated as follows: (1) by grouping the dishes and foods eaten into the following groups: A. fruit and vegetables; B. bread made of whole grain flour; C. dish made of meat, fish and/or eggs; and D. milk and milk products; (2) by sorting out the food combinations eaten by individuals; (3) by calculating the consumption of food raw materials per working day and per customer of the canteen based on the annual consumption reported by the employers. The figures obtained from (1) to (3) were compared with one third of the basic food group of the Pattern Dietary. According to the results only 21 % of the persons replying had eaten the combination A -)- B+C + D. Even these combinations did not always contain enough fruit and/or vegetables, and meat, fish and/or eggs. Since many also ate a nutritionally poor breakfast, they probably did not obtain sufficient quantities of several essential nutrients. Also the sodium/potassium equilibrium of the food seemed to be unfavourable, and the consumption of fats and saturated fatty acids was too high.